Thermography in ergonomic assessment: a study of wood processing industry workers - Soranso, Denise Ransolin; Minette, Luciano José; Marçal, Marcio; Marins, João Carlos Bouzas; Schettino, Stanley; Lima, Roldão Carlos A. [UNESP]; Oliveira, Michel (PeerJ, 2022)
Background. Workers in the wood processing industry perform activities that demand great physical and ergonomic demands, which favors the emergence of inflammatory processes and in turn the occurrence of heat regions in the body, thus making it possible to assess the inflammatory level by means of temperature gradients. This study aimed to evaluate the use of thermography as an ergonomic analysis tool to identify regions with musculoskeletal overload in workers in a wood processing industry. Methods. The study was conducted with nine workers in the central-west region of Brazil. The evaluations to obtain the thermographic images were carried out before the beginning of the workday, on Monday (day I) and on Friday (day II), in order to verify the overload regions in the accumulation of days worked. The thermal images were collected in an acclimatized room with controlled conditions where the participants remained with the upper part of their bodies bare for acclimatization, and then the lumbar and scapular regions were evaluated. The images were obtained using the FLUKE TI 400 Thermal Imager, with analysis using the SmartView software program to demarcate the body regions of interest. Results. The mean temperature values obtained on day I did not significantly differ from the mean values obtained on day II. Qualitative analysis showed thermal patterns with high temperature at the same points on both evaluated days. Although the thermographic analysis performed in this study cannot provide definitive results, they generally helped to provide evidence for a more accurate diagnosis in the evaluated workers.
Keywords: Occupational diseases; Thermal patterns; Wood splitting